A comprehensive review of diamond-reinforced metal matrix composites for thermal management in high-performance electronics - Abdul Wahid Shah; Kang Wang; Jabir Ali Siddique; Wenfang Li (Journal of Materials Research and Technology)
The development of novel thermal management materials (TIMs) is crucial for advancing GaN/SiC-driven high-power electronics, laser diodes, and RF electronics. Diamond-reinforced metal matrix (DRMM) composites have received significant attention in this regard due to the very high thermal conductivity (TC) and low coefficient thermal expansion (CTE) of diamond particles, making these composites ideal candidates for heat dissipation in electronics packaging. This review highlights the significant developments and ongoing efforts in the development of diamond-reinforced metal composites for thermal management, with a specific focus on diamond/metal interface engineering. It presents the chemistry and structure of different diamond surfaces, the importance of surface terminations, and the graphitization of diamond surfaces, explaining their impact on TC. Theoretical frameworks for calculating interface thermal conductance (ITC), TC, and CTE are summarized. The role of surface metallization and matrix alloying in achieving high TC, nearly matching theoretical calculations, is detailed through a comprehensive investigation of the wetting behavior of pristine and carbide-coated diamonds by molten metals and alloys. The review also elaborates on the design of microprocessor packages and the current materials used for various components. It discusses the feasibility of these composites as heat spreaders, packaging materials, and thermal interface materials in high-power electronics and RF devices, highlighting the advantages of diamond/metal composites over current commercial thermal management materials. Additionally, the challenges and future prospects of additive manufacturing (AM) techniques in producing these composites are reported. Research gaps in fundamental research and technology development are identified, and directions for future research are outlined.